2013
DOI: 10.2478/s11756-013-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

High frequency somatic embryogenesis and synthetic seed production of the endangered species Swertia chirayita

Abstract: An efficient protocol for plant regeneration through somatic embryogenesis was established from in vivo leaf explants of Swertia chirayita, a critically endangered medicinal herb. The highest frequency (76%) of embryogenic callus was induced on Murashige & Skoog (MS) medium supplemented with 0.5 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) and 0.5 mg/L kinetin (Kn) from in vivo leaf explants. Globular somatic embryos were induced and further matured from such embryogenic calli by subsequent culture on the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…It is believed that the development of efficient micropropagation protocols, can guarantee an adequate supply of S. chirayita plants (devoid of environmental-imposed constraints) with subsequent reduction in uncontrolled harvesting pressure on wild populations. Several studies reported on micropropagation, somatic embryogenesis and acclimatization procedures with the capacity to produce many uniform S. chirayita clones throughout the year (Kumar and Chandra, 2013 , 2014 ; Kumar et al, 2014 ). As shown in Table 5 , micropropagation protocols have successfully been established for S. chirayita using different explants.…”
Section: Swertia Chirayita Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the development of efficient micropropagation protocols, can guarantee an adequate supply of S. chirayita plants (devoid of environmental-imposed constraints) with subsequent reduction in uncontrolled harvesting pressure on wild populations. Several studies reported on micropropagation, somatic embryogenesis and acclimatization procedures with the capacity to produce many uniform S. chirayita clones throughout the year (Kumar and Chandra, 2013 , 2014 ; Kumar et al, 2014 ). As shown in Table 5 , micropropagation protocols have successfully been established for S. chirayita using different explants.…”
Section: Swertia Chirayita Conservationmentioning
confidence: 99%
“…Due to its excessive over-exploitation from the natural habitat, narrow geographic occurrence (Bhat et al, 2013 ) and unresolved inherent problems of seed viability and seed germination (Badola and Pal, 2002 ; Joshi and Dhawan, 2005 ), alternative approaches for propagation and conservation are urgently required to avoid the possible extinction of this important species. Consequently, S. chirayita has been receiving increasing attention from a wide range of researchers as evident from the number of publications appearing in the literature (Chen et al, 2011 ; Nagalekshmi et al, 2011 ; Ghosh et al, 2012 ; Kumar and Chandra, 2013 , 2014 , 2015 ; Fan et al, 2014 ; Kumar et al, 2014 ; Sharma et al, 2014 , 2015 ; Padhan et al, 2015 ; Zhou et al, 2015 ). However, a comprehensive review detailing the documented ethnomedicinal uses, pharmacological properties and safety evaluation carried out on S. chirayita and identifying the existing knowledge gap is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Direct organogenesis in S. chirayita was investigated by different explants such as nodal explants [1], shoot tip [7], leaf explants [8] and immature seed cultures [9]. Efficient regeneration protocols from shoot tip of field grown plants and high frequency somatic embryogenesis and regeneration from synthetic seed has previously published [10,11]. Callus induction from different explants of Swertia angustifolia and indirect regeneration from calli in Swertia mussotti was reported respectively [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Swertia chirayita, popularly known as "chirayata or chirayita", is considered to have diverse therapeutic properties, including anti-diabetic, anti-inflammatory, hypoglycemic, hepatoprotective, antibacterial, wound healing, antipyretic, antihelmintic, antioxidant and antitussive [12,13]. Large number of publications [14][15][16][17][18][19][20] in the research field clearly suggests the increasing importance and application of such important medicinal plant in various therapeutic fields. Brahmachari et al [21] clearly indicated Swertia genus as a rich sources of xanthones, flavonoids, irridoid, terpenoids and alkaloids.…”
Section: Introductionmentioning
confidence: 99%